Metodologia para la creacion de mercados para yuca en bolsa con ejemplos de Barranquilla, Colombia - Ostertag Gálvez, Carlos F. (International Center for Tropical Agriculture, 1988)
General information is presented on cassava cultivation in Colombia, trends in fresh cassava consumption, and fresh cassava conservation technology. The general objectives of creating markets for cassava packed in bags are also defined on the basis of the Barranquillan experience. The marketing approach is defined as well as the context of the proposed methodology, and component stages are explained: choice of target market, study of distribution structure, survey of consumer habits regarding use and purchase and of consumer attitudes, selection of production zones, on-farm trials, taste panels, business analysis, penetration plan, product development, publicity campaign, trial market/follow-up, and commercialization. For some stages, the experience acquired in Barranquilla is used as illustration. (CIAT)